New Classes of Generalized Seminormed Difference Sequence Spaces - M. Mursaleen; A. Alotaibi; Sunil K. Sharma (Abstract and Applied Analysis)
The purpose of this paper is to introduce new classes of generalized seminormed difference sequence spaces defined by a Musielak-Orlicz function. We also study some topological properties and prove some inclusion relations between resulting sequence spaces.